Relationship Between Life Event Stress, Social Support and Health For Women: Exploring the Impact of Social Support on Women's Health in the Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Indian society has been tremendously compound and itssocial and financial structures are considerably different. Social support hasimportant implications for the health and well-being of the aged. The aged inIndia has been providential in the sense that aged in India held a prestigiousposition in the family. The family support classification is very much intactin India, which gives support to all aged people. This paper focuses onassociation between life event stress, social support and health for women.